Epitaxial methods of quantum device growth - Muhammad, Rosnita; Othaman, Zulkafli; Sakrani, Samsudi; Wahab, Yussof (Faculty of Science, 2009)
Epitaxy is an affordable method for growing high quality crystalline in quantum device applications. The fabrication of the quantum devices is an outstanding challenge in nanostructure materials science. During last few years, a lot of attention has been devoted to the growth and characterization for low dimensional semiconductor materials. In this paper, we present several epitaxy methods in recent advancement. We then briefly examine the one and only epitaxial method that we have at Ibnu Sina Institute, Universiti Teknologi Malaysia i.e MOCVD system; starting with basic chemical reaction process, gas delivery equipment, reaction chambers and safety. Growth mechanisms and criteria for growth rate are also will be discussed. Lastly, we show gallium arsenide nanowires that succesfully grown using MOCVD system